Classification and nomenclature system for human alphapapillomavirus variants - Burk, Robert D. (Acta dermatovenerologica Alpina, Pannonica et Adriatica, 2011)
BACKGROUND: Papillomaviruses constitute a family of viruses that can be classified into genera, species and types based on their viral genome heterogeneity. Currently circulating infectious human Alphapapillomaviruses (alpha-PVs) constitute a set of viral genomes that have evolved from archaic times and display features of host co-speciation. Viral variants are more recently evolved genomes that require a standardized classification and nomenclature. OBJECTIVES: To describe a system for the classification and nomenclature of HPV viral variants and provide landmarks for the numbering of nucleotide positions. METHODS: The complete 8 kb genomes of the alpha-9 species group and HPV6 and 11 types, collected from isolates throughout the world were obtained from published reports and GenBank. Complete genomes for each HPV type were aligned using the E1 start codon and sequence divergence was calculated by global and pairwise alignments using the MUSCLE program. Phylogenetic trees were constructed from the aligned sequences using a maximumlikelihood method (RAxML). RESULTS: Pairwise comparisons of nucleotide differences between complete genomes of each type from alpha-9 HPV isolates (HPV16, 31, 33, 35, 52, 58 and 67) revealed a trimodal distribution. Maximum heterogeneity for variants within a type varied from 0.6%-2.3%. Nucleotide differences of approximately 1.0%-10.0% and 0.5%-1.0% of the complete genomes were used to define variant lineages and sublineages, respectively. Analysis of 43 HPV6 complete genomes indicated the presence of 2 variant lineages, whereas 32 HPV11 isolates were highly similar and clustered into 2 sublineages. A table was constructed of the human alpha-PV landmark nucleotidesequences for future reference and alignments. (Abstract truncated at 2000 characters).
Keywords: Base Sequence; Baze, zaporedje; Classification; Filogeneza; Genom virusni; Genome, Viral; Isolation And Purification; klasifikacija; Papilloma; Papillomavirus, Human; Papilom; papiloma virusi; Papilomavirus človeški; Phylogeny